Where the Boys Who Keep Swinging Are Now: Locational Relationality in Hedi Slimane and Helmut Lang - Ingram, Susan (Imaginations)

(untitled) (York University, 2018)
This article illustrates the mechanisms by which Berlin and Vienna have come to figure differently in the global fashion imaginary. It establishes the stylistic locational relationality of Hedi Slimane and Helmut Lang, two fashion designers known for distinctive styles that resist the mainstream of bourgeois respectability. The relational nature of their locational identities—Slimane’s attraction to Berlin and Lang’s rejection of Vienna—is tied to the cities’ urban imaginaries, which work by making particular periods and styles of the cities’ histories hegemonic.